Trajectories of plant-based diet indices and the associated risk of hypertension among Chinese adults: a cohort study based on the China Health and Nutrition Survey 2004–2015 - Yajie Zhao; Qian Gao; Junyan Zhang; Juping Wang; Tetsuya Araki; Junkang Zhao (Nutrition Journal)
Abstract Background Plant-based diets have been found to be associated with hypertension. Dietary intake is a dynamic and changing process that can be better characterized by trajectories of dietary indices. However, the associations between plant-based diet trajectories and hypertension over time remained unknown. Methods We used data from the China Health and Nutrition Survey 2004–2015 to analyze a cohort of Chinese adults ≥ 18 years of age who had no hypertension at baseline. Plant-based diets were measured by an overall plant-based diet index (PDI), healthful plant-based diet index (hPDI), and unhealthful plant-based diet index (uPDI) based on three 24-hour recalls. Trajectories of PDI, hPDI, and uPDI (2004 to 2011) were identified using group-based trajectory modeling. The associations between trajectories of PDIs and the risk of new-onset hypertension were estimated using Cox proportional hazard models. Results We identified three trajectories for PDI, two for hPDI, and four for uPDI among the 2853 participants with a mean follow-up of 9.6 years. Compared with the PDI “low and stable” class, the PDI “high and decreasing” class had a 23% decreased risk (HR: 0.77; 95% CI: 0.62–0.95) of hypertension. There was no significant association with PDI “low and increasing” class. Compared with the hPDI “low and stable” class, the hPDI “high and stable” class had a 24% decreased risk (HR: 0.76; 95%CI: 0.64–0.91). For uPDI trajectories, compared with the “low and decreasing” class, the “high and increasing,” “high and stable,” and “low and increasing” classes had increased risks of 43% (HR: 1.43; 95% CI: 1.06–1.94), 77% (HR: 1.77; 95% CI: 1.26–2.49), and 72% (HR: 1.72; 95% CI: 1.26–2.33), respectively. Conclusions This study underscores the importance of maintaining high intakes of healthful plant-based diets and low intakes of unhealthful plant-based diets overtime for hypertension prevention.